PENILAIAN KELAS DAN RASA PERCAYA DIRI SISWA PADA PEMBELAJARAN MATEMATIKA - CUT ASWADI (Jurnal Evaluasi Pendidikan, 2012)
This study aims to determine the effect of classroom assessment techniques with confidence mathematics students' learning outcomes. Classroom assessment techniques used are project appraisal and assessment of written tests. This research was conducted in MTsN Model Meulaboh and MTsN Blang Balee West Aceh district by using quasi experimental methods. Sampling was multistage random sampling technique as many as 48 students. Data were obtained through a questionnaire self-confidence of students and math achievement test. Data were analyzed using Analysis of Variance (ANOVA) with a two-lane design treatment by level 2 x 2 to see the main effect and interaction effect was followed by Tukey's test to test the simple effect. The study concluded that: (1) mathematics student learning outcomes assessment project given higher ratings than students who were given a written test, (2) there is an interaction effect between classroom assessment techniques with confidence mathematics students' learning outcomes, (3) results students were given a math project appraisal higher than students who were given a written assessment tests on groups of students that have a high confidence, and (4) for students who have low self-esteem, there is no difference in learning outcomes between students who were given math assessment projects with students who were given a written assessment test. In learning mathematics teachers are expected to use the project appraisal and materials tailored to students' self-confidence.